ChemInform Abstract: One‐Pot Cross Double‐Mannich Reaction of Acetaldehyde Catalyzed by a Binaphthyl‐Based Amino Sulfonamide. Issue 21 (2nd May 2013) - Kano, Taichi; Sakamoto, Ryu; Yamaguchi, Yukako; Itoh, Ken‐ichi; Maruoka, Keiji
Abstract Densely functionalized diamines having three contiguous stereocenters are synthesized in a stereoselective fashion in a one‐pot cross double‐Mannich reaction.